The effect of mineral content on the degree of deviation from radioactive equilibrium in the ancient uranium ores of the Ukraine - Valter, A.A.; Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Y.V.; Pisansky, A.I.; Storizhko, V.E. (Вопросы атомной науки и техники, 2007)
The degree of radioactive nonequilibrium of ores was found to increase in the following order in accordance with the varying mineral content: relatively coarse-grained uraninite (UO₂<n<₂.₂₅) - coffinite (USiO₄), brannerite (UTi₂O₆) - secondary finegrained coffinite, brannerite-secondary minerals of thin veins, boltwoodite ((Ca,Na,K)(UO₂)[SiO₃OH]1.5H₂O), and membranous uraninite (UO₂.₂₅). This is ascribed to a different loss of radioactive recoil atoms by crystals because of real crystals dimensions and defects and features of ideal atomic structure of minerals. Установлено, що ступінь радіоактивного порушення рівноваги руд росте уздовж слідуючого тренду зміни мінерального складу: відносно грубозернистий уранініт (UO₂<n<₂.₂₅) - коффініт (USiO₄), бранерит (UTi₂O₆) - вторинні дрібнозернисті коффініти, бранерити - вторинні мінерали тонких прожилків - болтвудиту ((Ca,Na,K)(UO₂)[SiO₃OH]1.5H₂O), плівковий уранініт (UO₂.₂₅). Це пояснюється різним ступенем втрати кристалами радіоактивних атомів віддачі, що визначається як особливостями реальних кристалів, так і атомною структурою мінералів. Установлено, что степень радиоактивной неравновесности руд растёт вдоль следующего тренда изменения минерального состава: относительно крупнозернистый уранинит (UO₂<n<₂.₂₅) - коффинит (USiO₄), браннерит (UTi₂O₆) - вторичные мелкозернистые коффинит, браннерит - вторичные минералы тонких прожилков - болтвудит ((Ca,Na,K)(UO₂)[SiO₃OH]1.5H₂O), плёночный уранинит (UO₂.₂₅). Это объяснено различной степенью потери кристаллами радиоактивных атомов отдачи, что определяется как особенностями реальных кристаллов, так и атомной структурой минералов.